Detection of pedophilia content online: a case study using Twitter - Coelho, Raphael Reis; Oliveira, Jonice (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2021)
Social media allows users to consume a wide range of topics and content, such as pornography. The consumption of pornography, as well as the problems associated with this type of material, has grown over the years, especially among adolescents. Now, another type of pornographic content has been widely consumed: child pornography. Are social media helping to spread this content? To understand this issue, a survey was conducted based on data regarding the consumption of child pornography extracted from Twitter in 2020, followed by a series of analyzes that show a possible impact of twitter on the dissemination and consumption of this type of content.